Consistent trace element distribution and mercury isotopic signature between a shallow buried volcanic-hosted epithermal gold deposit and its weathered horizon. (April 2020) - Yin, Runsheng; Pan, Xin; Deng, Changzhou; Sun, Guangyi; Kwon, Sae Yun; Lepak, Ryan F.; Hurley, James P.
Abstract: Trace elements and Hg isotopic composition were investigated in mineralized rocks, barren rocks, and mineral soils in the Xianfeng prospect, a shallow buried epithermal gold deposit in northeastern China, to understand whether this deposit has left a diagnostic geochemical fingerprint to its weathered horizon. All the rocks and soils display congruent patterns for immobile elements (large ion lithophile elements, high field strength elements, and rare earth elements), which reflect the subduction-related tectonic setting. Both mineralized rocks and soils showed common enrichment of elemental suite As–Ag–Sb–Hg, suggesting that the Xianfeng gold deposit has released these elements into its weathered horizon. Similar mercury isotopic composition was observed between mineralized rocks (δ 202 Hg: −0.21 ± 0.70‰; Δ 199 Hg: −0.02 ± 0.12‰; 2SD) and barren rocks (δ 202 Hg: −0.46 ± 0.48‰; Δ 199 Hg: 0.00 ± 0.10‰; 2SD), suggesting that mercury in the Xianfeng deposit is mainly derived from the magmatic rocks. Mineralized soils (δ 202 Hg: −0.44 ± 0.60‰; −0.03 ± 0.14‰; 2SD) and barren soils (δ 202 Hg: −0.54 ± 0.68‰; Δ 199 Hg: −0.05 ± 0.14‰; 2SD) displayed congruent Hg isotopic signals to the underlying rocks, suggesting limited Hg isotope fractionation during the release of Hg from ore deposit to soils via weathering. This study reveals evidence of a simple and direct geochemical link between this shallow buried hydrothermal deposit and its weathered horizon, and highlights that the weathering of shallow-buried hydrothermal gold deposits can release a substantial amount of heavy metals (e.g. Hg, As and Sb) to surface soil. Graphical abstract: Image 1 Highlights: Paired rocks and soils display congruent patterns for immobile elements. Soils display congruent Hg isotopic signals to the underlying rocks. Mineralized rocks and soils showed common enrichment of elemental suite As–Ag–Sb–Hg. Limited Hg isotope fractionation occurs during the release of Hg from ore deposit to soils via weathering.